Bacteremic community-acquired infections due to Klebsiella pneumoniae: clinical and microbiological presentation in New Caledonia, 2008–2013. (December 2015) - Melot, Bénédicte; Colot, Julien; Guerrier, Gilles
Highlights: Klebsiella pneumoniae is a dominant cause of severe community-acquired bacteremic infections in New Caledonia. The mortality rate remains high despite adequate management. Risk factors for a poor outcome include renal impairment, chronic liver disease, pneumonia, and isolated bacteremia. Further studies should investigate genetic susceptibility for a better understanding of invasive infection due to K. pneumoniae . Summary: Objectives: To provide data on severe bacteremic community-acquired infections due to Klebsiella pneumoniae in New Caledonia. Methods: All patients admitted with bacteremic community-acquired infections due to K. pneumoniae at the only tertiary medical center in New Caledonia, from 2008 to 2013, were included retrospectively in this study. Clinical and microbiological characteristics were analyzed, as well as risk factors for mortality. Results: The characteristics of 119 patients were analyzed. The most common clinical presentation was urinary tract infection (40 cases, 33%), followed by pneumonia (28 cases, 23%), deep abscesses (15 cases, 13%), liver abscess (12 cases, 9%), meningitis in (five cases, 4%), and endophthalmitis (two cases, 1%). Multiple localizations were reported in 18 cases (15%) and isolated bacteremia was reported in 22 cases (18%). The overall mortality rate was 22% (26/119) and the mortality rate in the intensive care unit was 33% (14/42). Renal impairment, chronic liver disease, pneumonia, and isolated bacteremia were independent risk factors for mortality. Conclusions: K. pneumoniae is a dominant cause of severe community-acquired bacteremic infection in New Caledonia. Physicians should be aware of the poor prognosis of any patient with a bacteremic K. pneumoniae infection and should monitor patients presenting with risk factors closely.